Stylistic Functions and Uses of Phonological Devices in The Family First Online Advertisements - Jumana Saad; Saja Al-A' assam (آداب الكوفة)
Commercial advertisements in magazines are used to grab the reader's attention, arouse desire, contribute towards satisfaction and motivate them to take the purchasing action. The current study is  Stylistic Functions and Uses of Phonological Devices in The Family First Online Advertisements. The analysis is conducted on six advertisements texts taken from the Family First Magazine. The study's main goal is to investigate and discuss the stylistic phonological devices that are mostly used in commercial advertisements of the Family First magazine to convince the readers and have impact on their memory to achieve certain stylistic effects. The results show that, based on Khan and Jabeen (2015) model at the phonological level, the advertisers rely on using assonance and consonance as the most stylistic phonological devices used in commercial advertisements of the Family First magazine to convince the readers and have impact on their memory to achieve certain effects.